ผลของโปรแกรมกลุ่มบำบัดตามแนวคิดการปรับความคิดและพฤติกรรมร่วม กับการฝึกอานาปานสติสมาธิต่อความวิตกกังวลในนิสิตพยาบาล - รักมณีวงศ์, ยุพาพักตร์; ปานสุวรรณ, กรกาญจน์; ด่านยุทธศิลป์, ชุลีกร; โพธิมาศ, นิศากร (Naresuan University Journal: Science and Technology (NUJST); Vol 21 No 1 (2013): January-March 2013, 2014)
“ภาวะวิตกกังวล” นับว่าเป็นปัญหาสุขภาพจิตที่สำคัญของนิสิตพยาบาลชั้นปีที่2 เนื่องจากเป็นชั้นปีแรกของการขึ้นฝึกปฏิบัติงานบนคลินิก การศึกษาครั้งนี้จึงมีวัตถุประสงค์เพื่อศึกษาผลของโปรแกรมกลุ่มบำบัดตามแนวคิดการปรับความคิดและพฤติกรรมร่วมกับ การฝึกอานาปานสติสมาธิต่อความวิตกกังวลในนิสิตพยาบาล กลุ่มตัวอย่างเป็นนิสิตพยาบาลชั้นปีที่2 คณะพยาบาลศาสตร์มหาวิทยาลัยนเรศวร ภาคการศึกษาปลาย ปีการศึกษา 2553 จำนวน 56 คน แบ่งเป็นกลุ่มทดลองและกลุ่มควบคุม กลุ่มละ 28 คน กลุ่มทดลองได้รับ โปรแกรมกลุ่มบำบัดที่ผู้วิจัยได้พัฒนาขึ้น ภายใต้กรอบแนวคิดการปรับความคิดและพฤติกรรม (Cognitive Behavioral Therapy; CBT) เครื่องมือที่ใช้ในการศึกษา มี2 ประเภท ได้แก่1) เครื่องมือที่ใช้ในโปรแกรมกลุ่มบำบัดที่ผู้วิจัยพัฒนาขึ้น คู่มือการฝึกการปรับเปลี่ยน ความคิดและอานาปานสติสมาธิ และสื่อการสอนสมาธิ สมุดบันทึกความคิดประจำวัน 2) เครื่องมือเก็บรวบรวมข้อมูล ได้แก่ แบบบันทึก ข้อมูลส่วนตัว แล ะแบบปร ะเมินคว ามวิตกกัง ว ล (State Anxiety & Trait Anxiety ของสปิลเบอร์เกอร์ (Speilberger’s, 1983) ฉบับภาษาไทย ซึ่งหาความเที่ยงคำนวณจากสูตรสัมประสิทธิ์แอลฟาของครอนบาค เท่ากับ 0.92 และ 0.8 ตามลำดับ สถิติเชิงคุณภาพที่ใช้ คือ ร้อยละและค่าเฉลี่ย เปรียบเทียบความแตกต่างของคะแนนความวิตกกังวลของนิสิตพยาบาลก่อนและหลังการทดลองและในระยะติดตาม ภายในกลุ่มเดียวกัน และระหว่างกลุ่มทดลองและกลุ่มควบคุมโดยใช้สถิติ t- test และวิเคราะห์ข้อมูลของแบบแผนความคิดลบ โดยใช้การวิเคราะห์เนื้อหา (content analysis) ผลการวิจัยพบว่า กลุ่มตัวอย่างที่ได้รับโปรแกรมฯ มีคะแนนความวิตกกังวลลักษณะ ประจำตัว และขณะปัจจุบัน ทั้งในระยะหลังการทดลองและระยะติดตาม ต่ำกว่าก่อนทดลองและกลุ่มควบคุม อย่างมีนัยสำคัญที่ .05 และพบว่านิสิตพยาบาลมีการตระหนักรู้ในตนเอง และมีแบบแผนความคิดยืดหยุ่นขึ้น ทำให้นิสิตสามารถเผชิญปัญหาได้อย่างมี ประสิทธิภาพ     “Anxiety” is important mental heath problem of the second years nursing students because it is the first time for clinical nursing practice. The purpose of study was to study the effects of group cognitive behavioral therapy program combining with breathing meditation on anxiety of nursing students. The subjects were 56 second year nursing students in their second semester in 2010 at Faculty of Nursing Naresuan University in Phitsanulok. Simple random sampling technique was used for both the experimental and control groups (28 each). The experimental group counseling program was developed by the investigator according to the concepts of Cognitive Behavioral Therapy (CBT) and combining with breathing meditation. The instruments were two kinds of tools used in this study : 1) One tool used was the program was developed by the investigator according to the concepts of CBT and combining with breathing meditation and the media for teaching breathing meditation. 2) The second tool used was a Demographic Data From, Satisfaction and Questionnaire. Anxiety Questionnaire based on Speilberger’s STAI-Form X (Thai version), Nursing Student’s diary records Cronbach’s Alpha Coefficient Formula for the Anxiety Questionnaire were 0.92 และ 0.82 respectively. Post testing was done immediately following the intervention. Descriptive statistics were used to assess the demographic information. The difference of nursing student’s anxiety mean scores between before and after intervention within groups and that of between the experimental and control groups was analyzed using t – test and content analysis of cognitive pattern of negative. This study shows that after given treatment by the group cognitive behavioral therapy program combining with breathing meditation did effectively reduce anxiety levels (state anxietyand trait anxiety) of nursing students and self awareness in Cognitive pattern of negative that help to facilitate their behavioral changes in dealing with the problem and to confront problems effectively.
Keywords: โปรแกรมกลุ่มบำบัดตามแนวคิดการปรับความคิดและพฤติกรรม; การฝึกอานาปานสติสมาธิ; ความวิตกกังวล; แบบแผนความคิดลบ; Cognitive Behavioral Therapy Program, Breathing Meditation Anxiety, Cognitive pattern of negative